The gender productivity gap: Evidence from the Indian informal sector - Ira N. Gang; Rajesh S. N. Raj; Kunal Sen; Myeong-Su Yun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We examine the patterns and correlates of the productivity gap between male-owned and female-owned firms for informal enterprises in India. Female-owned firms are on average 45 per cent less productive than male-owned firms, with the clearest productivity gaps observed at the lower end of the productivity distribution. Using decomposition methods, we find that about 73 per cent of the productivity gap can be explained by structural effect, with the remainder being due to differences in observable characteristics as captured by composition effect. We also find that among observable characteristics, the most important contributing factors explaining the gender productivity gap are firm characteristics, such as firm size, age of the firm, assistance from the government, registration with state authorities, working on a contract basis, and maintaining accounts. Male-owned firms are more advantaged in these characteristics than female-owned firms.
Keywords: J17; O17; O53; 330; gender; productivity gap; India; decomposition methods; informal sector